Treatment satisfaction with injectable disease-modifying therapies in patients with relapsing-remitting multiple sclerosis (the STICK study). - Oscar Fernández; Eduardo Duran; Teresa Ayuso; Luis Hernández; Inmaculada Bonaventura; Mireia Forner; STICK Study Investigators Group (PLoS ONE, 2017)
Treatment satisfaction in patients with relapsing-remitting multiple sclerosis (RRMS) may impact adherence and thus clinical outcomes. The objective of this study was to measure the satisfaction of patients with RRMS with injectable disease-modifying therapies (DMTs) and to evaluate the factors associated with treatment satisfaction.In this observational retrospective study conducted in the neurology departments of 35 hospitals throughout Spain, demographic data, disease characteristics, and information on treatment with injectable DMTs were collected at a single scheduled visit. Treatment satisfaction was assessed using the Treatment Satisfaction Questionnaire for Medication (TSQM), version 1.4. Patients also answered complementary questions about the factors that might affect treatment satisfaction. The data collected were analyzed descriptively. A regression model was used to explore the factors associated with treatment satisfaction.The study included 445 patients (mean±SD age, 41±10.2 years; two-thirds women). The percentages treated with each DMT were Avonex 28.5%, Rebif 44 μg 24.5%, Copaxone 22.5%, Betaferon 13.0%, Rebif22 μg 8.3% and Extavia 3.1%. The mean±SD overall satisfaction according to the TSQM was 68.8±18.6 and the highest overall satisfaction was reported for Rebif 22 μg (72.4±20.3) and the lowest for Extavia (61.7±23.7). In the regression analysis, rehabilitation, interference with social life, pain on injection and number of MS treatments received were significantly associated with a decrease in overall TSMQ score. A small but significant negative correlation was found between EDSS scores and TSMQ scores (rho = -0.11, p = 0.02) and effectiveness (rho = -0.17, p<0.001). A perceived inconvenience of injections was reflected by the stated preference of 83% for once-daily oral treatment over other administration routes.Patients on stable injectable DMT therapy were reasonably satisfied with their treatment. Our results suggest that the main source of dissatisfaction with the current treatment is the inconvenience of the administration regimen.